OVOL (one village one link): A rural development initiative based on cultural technology district model to address employment disparities through a community-based approach for social and economic sustainability - Maretaniandini, Sessa Tiara; Rajendra, Ricky Dina; Tsabita, Zalfa Aura (Social, Ecology, Economy for Sustainable Development Goals Journal, 2025)
Background: Villages are the foundation of sustainable development, encompassing both physical and non-physical potential that can drive national economic growth and the achievement of Sustainable Development Goals (SDGs) goals 8 and 10. With 83,971 villages in Indonesia, these rural areas contribute significantly to the country's development, contributing 74% to the achievement of national SDGs. However, employment gaps between villages and cities still remain, such as lack of access to employment opportunities, wage gap, and skill gap. This is exacerbated by the demand-supply of labor mismatch and various existing employment policy challenges. Methods: This research used a literature study approach by reviewing various sources from academic journals, official reports, statistics reports, and books relevant to employment disparity problems, previous policies implemented, best-practice, and the Hexa Helix stakeholders as the main actors. Analysis was conducted through a thematic approach to the relevant literature, which was then synthesized to develop a comprehensive solution in order to address employment disparities in Indonesia. Findings: The One Village One Link (OVOL) program---(1) digital center community-based approach, (2) rural development framework, and (3) rural digital center---is initiated with the aims to address this gap by promoting integrated development in villages. By utilizing the unique physical and non-physical potential of each village, OVOL seeks to create rural jobs, reduce wage and skill gaps, and promote inclusive rural economic growth. Conclusion: Through a holistic approach, One Village One Link (OVOL) comes as an innovative solution to overcome employment disparities problem by empowering local potential using the Cultural Technology District (CTD) Model. Novelty of This Study: OVOL serves as comprehensive solution in addressing employment disparities in Indonesia villages, integrating cultural and technological aspect with Cultural Technology District (CTD) Model as the best-practice through community based approach.